Bisphosphonate-associated osteonecrosis of the jaw 2 years after teeth extractions: A case report solved with non-invasive treatment - Gómez-Moreno, G.; Arribas-Fernández, M. C.; Fernández-Guerrero, M.; Boquete-Castro, A.; Aguilar-Salvatierra, A.; Guardia, J.; Botticelli, D.; Calvo-Guirado, J. L. (My University, 2014)
Bisphosphonates are a type of drugs known to inhibit bone resorption through complex interventions. Their primary mechanism of action is aimed at the cellular level, inhibiting osteoclast activity and, thus, bone resorption. Bisphosphonates are, therefore, very widely used, with many patients receiving continuous treatment for years. But it is well known that these drugs can produce osteonecrosis of the jaw and this is their principal risk. A 75-year-old woman received dental treatment before starting intravenous BP therapy for a breast cancer. She started intravenous bisphosphonate treatment with monthly protocol and after two years the patient presented a wound compatible with osteonecrosis of the jaw.
Keywords: Bisphosphonates; Chlorhexidine; Osteonecrosis of the jaw